From symbols of oppression to marks of freedom: the preservation of brazilian colonial pillories and the silencing of slavery’s memory (XVI-XXth centuries) - Andrade, Francisco (Revista de História, 2022)
The history of colonial pillories (a landmark that symbolized municipal autonomy and served as a place for physical punishments) remains largely unknown — usually, they are mentioned in local monographs or urban history textbooks often based on reckless generalizations from a few better known examples or on mere assumptions. Given the impossibility of drawing an overview of the history of Brazilian pillories, this article intends only to establish a interpretative guideline about their meaning in the Luso-Brazilian urban culture and the contexts that influenced their destruction throughout the XIX century. Then, it seeks to analyze some cases of urban preservation or musealization of colonial pillories and the erasure of slavery’s memory in Brazil.